A Barn on the Bank of a Stream in Gelderland - Auteur inconnu (Rijksmuseum)
Oeuvre issue des collections Rijksmuseum / Orsay via Europeana pour la demo du fonds documentaire.
Droits : http://creativecommons.org/publicdomain/mark/1.0/
Keywords: rijksmuseum; orsay; europeana; oeuvre d'art; musee; Peintures